The Paradox of Microplastic Removal in WWTP: Redistribution of Micropollutants in the Environment - Zdarta, Agata; Li, Guoqiang (Current pollution reports, 2025)
Purpose of the Review High amounts of microplastics (MPs) are collected and then disposed of in sewage treatment plants. This review aims to identify the effects of wastewater treatment processes on the physical and chemical properties of MPs as well as their fragmentation and ageing, which are rarely reported and have not yet been revised. Recent Findings The amount of microplastic particles introduced into the WWTP depends on many factors, such as the area and population, treatment processes, migration of people, and weather conditions. As a result, WWTP effluents were identified as the source of MP pollution. Selected treatment methods and chemicals used in wastewater treatment may contribute to the deterioration of MP. Summary The impact of individual physical, mechanical, and chemical factors on the fate of microplastics in the WWTP was analysed. In the case of preliminary and primary treatment processes, the fragmentation of MP particles is mainly affected by mechanical interactions such as physical abrasion and water shearing force. However, during tertiary treatment processes, chemical factors such as advanced oxidation processes, chlorination, and ozonation play a leading role in MP deterioration. The paradox of so-called microplastic removal in WWTPs has been highlighted, and the concept of defining wastewater treatment plants as sources of tertiary microplastic pollution has been proposed. Graphical Abstract